Study of Palatal Rugae Pattern in Student Population - Chaphu Chimyang, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Palatal Rugae have individual characteristics and unique in nature. Therefore, can be used as a parameter in forensics. Palatal Rugae and the technique of personal identification with the help of this can provide an investigative tool in forensic science. Present study was conducted at Dept. of Forensic Science, Sharda University and College of Dental Science, Manav Rachna International Institute of Research and Studies, Faridabad. The study includes 120 subjects of age more than 18 years. The maxillary alginate impressions were obtained on perforated metal trays. Casts were poured using dental stone. Palatal rugae were outlined using a pencil and magnifying glass. The data was analyzed using Statistical Package for Social Sciences (SPSS), Version 22.0. The minimum rugae count on both sides was found one while it was maximum on the right side. Maximum and minimum number of rugae in study population was seven and three respectively with mean 4.81. The predominant rugae form in the study population was Curvy (57.5%) followed by wavy pattern (30%) and circular (10%). Palatal rugae possess the characteristic to be used for forensic investigation because of its uniqueness.